CONTEXTUAL REDEFINITION : A TEACHING STRATEGY FOR ENHANCING BEGINNER LEVEL OF READING ACHIEVEMENT - Dina Merris Maya Sari (Journal of English Educational Study (JEES), 2020)
Reading is the most important skill for both English as a Second Language (ESL) and English as a Foreign Language (EFL) learners especially in academic context, because the students need to comprehend and deal with al reading aspects and diffculties. Departing from those needs, so it takes a strategy in teaching reading, especially basic reading. Contextual  Redefinition is a strategyof  teaching that helps students learn the significance of  context  clues  in  understanding  the  meaning  of  a  word  or  concept. This research design is classroom action research. This study purposes to determine the extent to which the Contextual Redefinition strategy can improve students' vocabulary mastery and to find out factors of increasing students' vocabulary mastery. The subjects of this study were 26 English Education students of first semester. The research instruments were vocabulary tests, observation checklists and field notes, and questionnaire. Based on the results of the vocabulary test, there was an increase in students' vocabulary mastery from 30.77% at the beginning of the data to 42.30% in cycle 1 and 65.38% in cycle 2. The factors that increased students' vocabulary mastery were educator factors (class management) and students' factors (interests, enthusiasm, participation, and attention).